Education Prevention and Treatment Injury to MGMP PJOK SMP Magelang City - Yuwono, Cahyo; Supriyono, Supriyono; Baskora, Ranu; Sudarmono, Martin (Jurnal Abdimas, 2023)
Problem priorities faced by MGMP SMP partners throughout Magelang City is Lack of knowledge and practice handler injury at school ; Lack of Physical education teachers' concern For handle and care for injury moment Learning . So that solution offered _ is Stage counseling about Prevention and treatment Injuries to MGMP Middle Schools in Magelang City ; Stage socialization knowledge about prevention and treatment injury First moment the learning . By general implementation activity use Aras Mezzo approach , namely empowerment done with use group as an intervention medium : education and training, as well dynamics divided groups _ become three stages , ie stage preparation , stage implementation , and stages evaluation and monitoring. As for effort For program sustainability is through socialization knowledge about prevention and treatment injury.